2022
DOI: 10.56557/upjoz/2022/v43i213210
|View full text |Cite
|
Sign up to set email alerts
|

TOXICO-PATHOLOGICAL ASSESSEMENT OF Nerium oleander ROOTS AND LEAVES ON WISTAR RAT

Abstract: The aim of the study was to evaluate the toxic effects of Nerium oleander roots (R) and leaves (L) aqueous extract on Wistar rat. Serum chemistry, epididymal sperm parameters and histological examination of liver, kidney and brain were assessed after twelve consecutive day’s oral administration of N. oleander. The extracts of R1, R2, L1 and L2 induced no treatment-related adverse effects with regard to general behaviors, hematological, serum chemistry, epididymal sperm parameters and histological profiles of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…It is reported that Nerium oleander have properties of rodenticide (Bari et al, 2020), piscicides (Tiwari and Singh, 2004) and larvicides (Behravan et al, 2017). Toxicity of these plants can block heart function and nervous system of living organisms because of irregular function of Na/K-ATPase channel (Maarauf et al, 2022). Nerium have antiulcer (Patel et al, 2010), anti-inflammatory and antipyretic properties (Kumar and Anand, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Nerium oleander have properties of rodenticide (Bari et al, 2020), piscicides (Tiwari and Singh, 2004) and larvicides (Behravan et al, 2017). Toxicity of these plants can block heart function and nervous system of living organisms because of irregular function of Na/K-ATPase channel (Maarauf et al, 2022). Nerium have antiulcer (Patel et al, 2010), anti-inflammatory and antipyretic properties (Kumar and Anand, 2010).…”
Section: Introductionmentioning
confidence: 99%